GLP‐2 as Beneficial Factor in the Glucose Homeostasis in Mice Fed a High Fat Diet. Issue 12 (24th August 2015) - Baldassano, Sara; Rappa, Francesca; Amato, Antonella; Cappello, Francesco; Mulè, Flavia
<x xml:space="preserve">Abstract</x> Glucagon like peptide‐2 (GLP‐2) is a gastrointestinal hormone released in response to dietary nutrients, which acts through a specific receptor, the GLP‐2 receptor (GLP‐2R). The physiological effects of GLP‐2 are multiple, involving also the intestinal adaptation to high fat diet (HFD). In consideration of the well‐known relationship between chronic HFD and impaired glucose metabolism, in the present study we examined if the blocking of the GLP‐2 signaling by chronic treatment with the GLP‐2R antagonist, GLP‐2 (3–33), leads to functional consequences in the regulation of glucose metabolism in HFD‐fed mice. Compared with animals fed standard diet (STD), mice at the 10th week of HFD showed hyperglycaemia, glucose intolerance, high plasma insulin level after glucose load, increased pancreas weight and β cell expansion, but not insulin resistance. In HFD fed mice, GLP‐2 (3–33) treatment for 4 weeks (from the 6th to the 10th week of diet) did not affect fasting glycaemia, but it significantly increased the glucose intolerance, both fasting and glucose‐induced insulin levels, and reduced the sensitivity to insulin leading to insulin‐resistance. In GLP‐2 (3–33)‐treated HFD mice pancreas was significantly heavier and displayed a significant increase in β‐cell mass in comparison with vehicle‐treated HFD mice. In STD mice, the GLP‐2 (3–33) treatment did not affect fasted or glucose‐stimulated glycemia, insulin, insulin sensitivity, pancreas weight and beta cell mass. The present study suggests that endogenous GLP‐2 may act as a protective factor against the dysregulation of the glucose metabolism that occurs in HFD mice, because GLP‐2 (3‐33) worsens glucose metabolism disorders. J. Cell. Physiol. 230: 3029–3036, 2015. © 2015 Wiley Periodicals, Inc.